1952
DOI: 10.1172/jci102628
|View full text |Cite
|
Sign up to set email alerts
|

Renal Clearances of Grass Polysaccharide: Observations on Glomerular Porosity and on the Relation of This Function to Proteinuria in Renal Disease

Abstract: bridge, drew our attention in 1948 to a fructosan polysaccharide (levan) prepared from Italian rye grass. It is readily soluble in cold water, yields levulose on acid hydrolysis and is not metabolized. At that time, the fructosan was believed to be a homogeneous substance with a molecular weight somewhat greater than that of inulin, so that the suggestion was made that it might replace inulin in the measurement of glomerular filtration rate. It has since (see below) been shown to be inhomogeneous. Samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
4
0

Year Published

1953
1953
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
4
4
0
Order By: Relevance
“…The clearance of the polysaccharide fructosan (approximate mol wt 8,000) equals that of inulin in normal man, but averages only 60% of GFR in patients with glomerular disease, and similar observations have been made for a second larger polysaccharide (40). In addition, the ratios of hemoglobin (mol wt 68,000) to inulin clearances are reduced below normal in proteinuric patients with the nephrotic syndrome (41).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The clearance of the polysaccharide fructosan (approximate mol wt 8,000) equals that of inulin in normal man, but averages only 60% of GFR in patients with glomerular disease, and similar observations have been made for a second larger polysaccharide (40). In addition, the ratios of hemoglobin (mol wt 68,000) to inulin clearances are reduced below normal in proteinuric patients with the nephrotic syndrome (41).…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, the GBM itself appears to completely separate plasma from the glomerular filtrate. Traditionally this structure has been considered to behave as a semipermeable membrane containing cylindrical pores of [35][36][37][38][39][40][41][42] A radius or rectilinear slits of half-width 36 A (5). However, if the membrane does contain functional pores, it may be more heteroporous than originally suggested (6), and although these experiments suggest that the basement membrane contains pores, such pores have never been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…These results have been confirmed and extended in a later paper [Beattie and Corcoran, 1952] [1925] from iris rhizomes grown in Essex, England.B. The two bacterial levans were isolated from the growth media of the appropriate micro-organisms.…”
supporting
confidence: 75%
“…and details of two of these are given in Table I Irisin Partition Experiments. Beattie and Corcoran [1952] suggested that irisin may consist of two or more components with differing rates of clearance. To obtain further information, the fructosan excreted during the first hour after injection was recovered and injected into a second animal.…”
Section: Observations and Resultsmentioning
confidence: 99%
See 1 more Smart Citation